Daya Saing Usaha Mikro Kecil : Modifikasi Porter Diamond Model - Rustian, Lita Apriani; Widiastuti, Tantri (STIE Widya Manggala, 2020)
This study aims to analyze: (1) the effect of production factors on competitiveness; (2) the effect of demand conditions on daylight power (3) the effect of related and supporting industries on competitiveness (4) the effect of production factors, demand conditions and related and supporting industries on competitiveness. Respondents in this study were 90 micro and small businesses that became partners of Pusat Layanan Usaha Terpadu (PLUT) in the Special Region of Yogyakarta. The variables used in this research are related and supporting industrial cooperation as independent variables, production factors, demand conditions, competitiveness as the dependent variable. Data collection using questionnaires and data analysis using multiple linear regression analysis. The results of the research are showed that, production factors have an effect on MSE competitiveness of 6.05%, demand conditions of 11.28% and related and supporting industries of 8.58%.